Performance of Youth Entrepreneurs In Malaysia Micro Small and Medium Enterprises - Khan, Shazida Jan Mohd; Noor, Nur Syamilah Md.; Anuar, Abdul Rahim (International Journal of Economics and Financial Issues, 2016)
This study aims to look on the role of government policy, infrastructure, and business support facility towards the performance of youth entrepreneurs involved in micro SMEs in Malaysia. Entrepreneurship development calls for support from various quarters and primarily the need exists to initiate a youth entrepreneurship culture and drive amongst the youth in the society. The study adopts a quantitative approach whereby a questionnaire survey was used to gather data. Seemingly unrelated regression (SURE) was chosen as a method of analysis and the result of this study is expected to give insight into the existing government policy, infrastructure, and business support facility while assisting in formulation policies for the development of youth entrepreneur specifically involved in micro SMEs. Keywords: Youth Entrepreneur; micro SMEs; infrastructure facility; business support facility; government policy JEL Classifications: L2, L26